Plasma electrolytic oxidation of Titanium Aluminides. Issue 1 (March 2016) - Morgenstern, R; Sieber, M; Grund, T; Lampke, T; Wielage, B
Abstract: Due to their outstanding specific mechanical and high-temperature properties, titanium aluminides exhibit a high potential for lightweight components exposed to high temperatures. However, their application is limited through their low wear resistance and the increasing high-temperature oxidation starting from about 750 °C. By the use of oxide ceramic coatings, these constraints can be set aside and the possible applications of titanium aluminides can be extended. The plasma electrolytic oxidation (PEO) represents a process for the generation of oxide ceramic conversion coatings with high thickness. The current work aims at the clarification of different electrolyte components' influences on the oxide layer evolution on alloy TNM-B1 (Ti43.5Al4Nb1Mo0.1B) and the creation of compact and wear resistant coatings. Model experiments were applied using a ramp-wise increase of the anodic potential in order to show the influence of electrolyte components on the discharge initiation and the early stage of the oxide layer growth. The production of PEO layers with technically relevant thicknesses close to 100 μm was conducted in alkaline electrolytes with varying amounts of Na2 SiO3 ·5H2 O and K4 P2 O7 under symmetrically pulsed current conditions. Coating properties were evaluated with regard to morphology, chemical composition, hardness and wear resistance. The addition of phosphates and silicates leads to an increasing substrate passivation and the growth of compact oxide layers with higher thicknesses. Optimal electrolyte compositions for maximum coating hardness and thickness were identified by statistical analysis. Under these conditions, a homogeneous inner layer with low porosity can be achieved. The frictional wear behavior of the compact coating layer is superior to a hard anodized layer on aluminum.